2011
DOI: 10.4028/www.scientific.net/kem.467-469.1776
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Modal Analysis in Hole-Defect in Lumber

Abstract: Larch lumbers were tested by using modal analysis technology and Frequency response functions (FRF) were derived. Modal parameters, including first 4 intrinsic frequency and first 3 modal shape, were distinguished by single modal method. Research shows that the intrinsic frequency of hole-defect lumbers is little lower than standard lumbers’ and the change rate of frequency is becoming larger gradually with the diameter of hole-defect. However, it can not judge the position of the hole-defect by the change rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Despite the extensive studies of vibration nondestructive analysis on damaged wood-based composites, only a few effective and practical techniques were found for position and degree identification of wood-based composites damage (Choi et al 2007;Roohnia et al 2014;Reinprecht and Hibký 2011). Modal analyses has proven to be an effective method for defects detection (Khademieslam et al 2011;Ma et al 2008;Song et al 2011). Therefore, this paper focuses on the study of a practical method for effective detection of bubble defects in poplar LVL by combining wavelet packet energy curvature method with 3-scale wavelet packet decomposition of nondestructive vibration signals.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive studies of vibration nondestructive analysis on damaged wood-based composites, only a few effective and practical techniques were found for position and degree identification of wood-based composites damage (Choi et al 2007;Roohnia et al 2014;Reinprecht and Hibký 2011). Modal analyses has proven to be an effective method for defects detection (Khademieslam et al 2011;Ma et al 2008;Song et al 2011). Therefore, this paper focuses on the study of a practical method for effective detection of bubble defects in poplar LVL by combining wavelet packet energy curvature method with 3-scale wavelet packet decomposition of nondestructive vibration signals.…”
Section: Introductionmentioning
confidence: 99%
“…Previous authors (CAM et al, 2004;DIVOS et al, 2001;SOBUE et al, 2010;SONG et al, 2011) studied the influence of defect on the dynamic behavior of wood in order to detect and positioned the local heterogeneities. Divos et al (2001), by the means of a time analysis technique, showed that the amplitude of the received signal was more sensitive to the presence of defect than the measurement of the propagation velocity.…”
Section: Introductionmentioning
confidence: 99%
“…The defect position was well identified, but the procedure was limited to the identification of two dominant defects. Song et al (2011) used a modal analysis technique allowing the determination of the mode shapes and resonance frequencies. They were not able to determine the position of the defect by the change rate of frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Sobue et al (2010) exploited an inverse solution procedure enabling the identification of the defect position within a beam, which was made possible by the resonance frequency of longitudinal vibrations. Song et al (2011) tested larch lumber pieces using a modal analysis technique, while frequency response functions (FRF) were derived. In their approach, modal parameters, including the first four natural frequencies and the first three modal shapes, were distinguished by the single modal method.…”
Section: Introductionmentioning
confidence: 99%